Activated regulatory T cell regulates neural stem cell proliferation in the subventricular zone of normal and ischemic mouse brain through interleukin 10 - Wang, Jixian; Xie, Luokun; Yang, Chenqi; Ren, Changhong; Zhou, kaijing; Wang, Brian; Zhang, Zhijun; Wang, Yongting; Jin, Kunlin; Yang, Guo-Yuan (Frontiers in Cellular Neuroscience, 2015)
Recent studies have demonstrated that the depletion of Regulatory T cells (Tregs) inhibits neural progenitor cell migration after brain ischemia. However, whether Tregs affect neural stem/progenitor cell proliferation is unclear. We explored the effect of Tregs on neurogenesis in the subventricular zone after ischemia. Tregs were isolated and activated in vitro. Adult male C57BL/6 mice underwent 60 minutes transient middle cerebral artery occlusion (tMCAO). Then Tregs (1x105) were injected into the left lateral ventricle of normal and ischemic mouse brain. Neurogenesis was determined by immunostaining. The mechanism was examined by inhibiting interleukin 10 (IL-10) and transforming growth factor (TGF-) signaling. We found that the number of BrdU+ cells in the subventricular zone was significantly increased in the activated Tregs-treated mice. Double immunostaining showed that these BrdU+ cells expressed Mash1. Blocking IL-10 reduced the number of Mash1+/BrdU+ cells, but increased the amount of GFAP+/BrdU+ cells. Here we conclude that activated Tregs enhanced neural stem cell proliferation in the subventricular zone of normal and ischemic mice; blockage of IL-10 abolished Tregs-mediated neural stem cell proliferation in vivo and in vitro. Our results suggest that activated Tregs promoted neural stem cell proliferation via IL-10, which provides a new therapeutic approach for ischemic stroke.